Molecular Iodine: A Powerful Catalyst for the Knoevenagel Condensation of Isatins with Malononitrile - Xiao Juan Yang; Yong Sen Zhang (Journal of Chemistry)
Molecular iodine has been used as an efficient catalyst for an improved and rapid condensation of isatins with malononitrile in excellent yields. The significant features of the iodine-catalyzed Knoevenagel condensation are operational simplicity, inexpensive reagents, high yield of products, and the use of nontoxic reagents.